Pharmacokinetics of Povidone-Iodine and Its Effects on Bacterial Keratitis - Rezandi Aziztama (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2021)
The purpose of this study was to investigate the pharmacokinetics and safety of povidone-iodine and its efficacy against bacterial keratitis. The method in phase I, forty New Zealand white rabbits were divided into groups I and II and received intravitreal 0.1% and 0.3% PVI, respectively. Electroretinography (ERG) and histologic examinations were conducted at baseline, 6, and 12 hours. Half-life was determined using high- performance liquid chromatography. In phase II, after the induction of S. epidermidis, 0.1% and 0.3% PVI were injected intravitreally once in groups A and B and three times every second day in groups C and D (n 10 in each group). Electroretinographs, histologic examinations, and vitreous cultures were conducted on day 14. Electroretinography and histologic examinations did not reveal any notable retinal damage in phase I in either group. Half-lives were 3.27 and 3.58 hours in groups I and II, respectively. In phase II, all groups demonstrated marked improvement, compared to controls. Bacterial growth was found in four eyes in group A (20, 60, 60, and 70 colony forming units [CFU]) and in three eyes in group B (20, 40, and 60 CFU) but not in those belonging to groups C and D at day 14. Retinal damage with lymphocyte infiltration in the inner retinal layers was more common in groups A and B than in groups C and D. Half-life of PVI was approximately 3 hours in the vitreous. Repeated injection of intraocular PVI, even at low concentrations, is most likely to be effective for the treatment of bacterial endophthalmitis.